2022
DOI: 10.1093/brain/awac317
|View full text |Cite
|
Sign up to set email alerts
|

The use of optical coherence tomography in neurology: a review

Abstract: Optical coherence tomography (OCT) is a non-invasive, cost-efficient technique that provides high-resolution in vivo imaging of retinal tissue. The peripapillary retinal nerve fibre layer (pRNFL) and macular ganglion cell complex (mGCC) are surrogate markers of neuroaxonal integrity in not only the eye, but also the central nervous system. Retinal atrophy may occur in tandem with central nervous system pathologies as a result of injury to ganglion cells, direct degeneration of the pregeniculate pathway, or ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 216 publications
1
21
0
Order By: Relevance
“…RNFL and GCIPL thicknesses are indicators of retinal ganglion cell structure integrity, 29 where the RNFL comprises retinal ganglion cell axons whereas the GCIPL comprises the cell bodies and dendrites of the retinal ganglion cells 30 . The ONH is the main ocular site for IH thus, an insult to the ONH causes atrophy ultimately leading to thinning of these neuronal layers during IH 31 as seen in our study.…”
Section: Discussionsupporting
confidence: 69%
“…RNFL and GCIPL thicknesses are indicators of retinal ganglion cell structure integrity, 29 where the RNFL comprises retinal ganglion cell axons whereas the GCIPL comprises the cell bodies and dendrites of the retinal ganglion cells 30 . The ONH is the main ocular site for IH thus, an insult to the ONH causes atrophy ultimately leading to thinning of these neuronal layers during IH 31 as seen in our study.…”
Section: Discussionsupporting
confidence: 69%
“…These layers can be individually segmented in vivo in cross-sectional scans, and their thickness quantified with a non-invasive and reproducible technology called optical coherence tomography (OCT), that achieves a high resolution in cross-sectional images ( Figure 1 a), similar to that obtained in histological sections [ 11 ]. OCT technology has been extensively used to study biomarkers in other CNS disorders [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The axons of RGCs form the optic nerve, which extends to the thalamus and the midbrain. Studies have shown that retinal atrophy may occur in conjunction with CNS pathologies, due to injury to ganglion cells, direct degeneration of the pregeniculate pathway or retrograde trans-synaptic degeneration secondary to postgeniculate lesions 8…”
Section: Introductionmentioning
confidence: 99%
“…Notably, studies have employed OCT images to reveal retinal changes in neurodegenerative diseases, including thinning of the retinal nerve fibre layer (RNFL) 9 10. Peripapillary RNFL and macular ganglion cell complex (GCC) thickness measured by OCT have been applied to efficiently diagnose and monitor neurological disorders 8. Ong et al 11 reported that retinal neuronal damage was associated with grey matter atrophy, suggesting that retinal changes could reflect neurodegenerative changes in the brain.…”
Section: Introductionmentioning
confidence: 99%